Genetic and epigenetic interplay allows rapid transgenerational adaptation to metal pollution in zebrafish. Issue 1 (22nd October 2022) - Pierron, Fabien; Heroin, Débora; Daffe, Guillemine; Daramy, Flore; Barré, Aurélien; Bouchez, Olivier; Romero-Ramirez, Alicia; Gonzalez, Patrice; Nikolski, Macha
Abstract: Despite still being a matter of debate, there is growing evidence that pollutant-induced epigenetic changes can be propagated across generations. Whereas such modifications could have long-lasting effects on organisms and even on population, environmentally relevant data from long-term exposure combined with follow-up through multiple generations remain scarce for non-mammalian species. We performed a transgenerational experiment comprising four successive generations of zebrafish. Only fish from the first generation were exposed to an environmentally realistic concentration of cadmium (Cd). Using a whole methylome analysis, we first identified the DNA regions that were differentially methylated in response to Cd exposure and common to fish of the first two generations. Among them, we then focused our investigations on the exon 3 (ex3) of the cep19 gene. We indeed recorded transgenerational growth disorders in Cd-exposed fish, and a mutation in this exon is known to cause morbid obesity in mammals. Its methylation level was thus determined in zebrafish from all the four generations by means of a targeted and base resolution method. We observed a transgenerational inheritance of Cd-induced DNA methylation changes up to the fourth generation. However, these changes were closely associated with genetic variations, mainly a single nucleotide polymorphism. This single nucleotide polymorphism was itself at the origin of the creation or deletion of a methylation site and deeply impacted the methylation level of neighboring methylation sites. Cd-induced epigenetic changes were associated with different mRNA transcripts and an improved condition of Cd fish. Our results emphasize a tight relationship between genetic and epigenetic mechanisms and suggest that their interplay and pre-existing diversity can allow rapid adaptation to anthropogenic environmental changes.